Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Balai Kota Among Tani Batu - Hilaria Wahon; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to analyze the effect of training and work discipline on employee performance at the city hall amongtani Batu. The population used in this study are all employees who work at the Among Tani city hall Batu in the human resources departement. The sampling technique used saturated sample technique method obtained a sample of 19 respondents. The data collection method in this study used the questionnaire method.Through this research, it can be concluded effect of training and work discipline has a simultaneoud and significant effect on employee performance , effect of training indirectly has a significant effect on employee performance, work discipline has a significant effect on employee performance at the city hall Among Tani Batu. keywords : training, work discipline, employee performance